2013
DOI: 10.7314/apjcp.2013.14.10.6041
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Breast Cancer Screening Behavior in Japan - Assessment using the Health Belief Model and Conjoint Analysis

Abstract: Background: Japanese women in their 40s or older have been encouraged to attend breast cancer screening. However, the breast cancer screening rate in Japan is not as high as in Europe and the United States. The aim of this study was to identify psychological and personal characteristics of women concerning their participation in breast cancer screening using the Health Belief Model (HBM). In addition, the attributes of screening more easily accepted by participants were analyzed by conjoint analysis. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Its validity and reliability has been replicated among several racial and Asian ethnic minority populations across the world (Champion et al, 2008;Parsa et al, 2008;Anagnostopoulos et al, 2012;Tsangari and Petro-Nustas, 2012;Fouladi et al, 2013;Subramanian et al, 2013;Tsunematsu et al, 2013). While much of the prior work done to examine attitudes and beliefs towards cancer and screening among South Asians has been limited to small qualitative studies (Kishore et al, 2008;Karbani et al, 2011), this is the first community sample from two large metropolitan cities in the US that used constructs from the HBM to examine breast cancer screening attitudes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Its validity and reliability has been replicated among several racial and Asian ethnic minority populations across the world (Champion et al, 2008;Parsa et al, 2008;Anagnostopoulos et al, 2012;Tsangari and Petro-Nustas, 2012;Fouladi et al, 2013;Subramanian et al, 2013;Tsunematsu et al, 2013). While much of the prior work done to examine attitudes and beliefs towards cancer and screening among South Asians has been limited to small qualitative studies (Kishore et al, 2008;Karbani et al, 2011), this is the first community sample from two large metropolitan cities in the US that used constructs from the HBM to examine breast cancer screening attitudes.…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed a disturbing pattern of reduced perception among South Asians to their susceptibility to breast cancer in spite of increased risks associated with changing lifestyles and environmental exposures. Studies from other Asian populations (e.g., Japanese) that have much higher screening rates (64%) show that awareness of cancer screening benefits along with lower barriers to obtaining screening are crucial to motivating participation in breast cancer screening (Tsunematsu et al, 2013). A systematic review of the literature shows that interventions on breast cancer screening that were adapted from the HBM, obtained positive changes in screening behavior when nurses employed components of the HBM to promote awareness of early screening (Ersin and Bahar, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MHLW reported that implementing cancer screening and specific health checkups simultaneously improved cancer screening rates in some municipalities (MHLW, 2012b). In addition to these strategies, future studies that determine other effective strategies for improving cancer screening rates are warranted, including where screening occurs and the medical personnel involved (Tsunematsu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the reason behind people's not having a positive attitude towards cancer prevention and early diagnosis is important in cancer prevention research. There are many scientific researches to prevent breast cancer, cervical cancer and colorectal cancer by using health belief model (Gozum et al, 2004;Gercek et al, 2008;Kilic et al, 2009;Gozum et al, 2010;Aydogdu and Bahar, 2011;Ersin and Bahar, 2011;Tasci-Duran, 2011;Fouladi et al, 2013;Tsunematsu et al, 2013;Kharameh et al, 2014). Nevertheless, in general, there are no research related to cancer prevention and early diagnosis using health belief model.…”
Section: Turkish Social Attitudes Towards To Cancer Prevention: a Heamentioning
confidence: 99%